Wellness choices for health & fitness - Donatelle, Rebecca J. (Wodsworth, 1999)
This text presents balanced and in-depth information on all dimensions of wellness. Built on a text of academic content and pedagogy, the revision explicitly focuses on wellness throughout, includes more pedagogy and has a new interior design.